2021
DOI: 10.1167/iovs.62.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Biometrics, Impact, and Significance of Basal Linear Deposit and Subretinal Drusenoid Deposit in Age-Related Macular Degeneration

Abstract: Basal linear deposit (BLinD) is a thin layer of soft drusen material. To elucidate the biology of extracellular deposits conferring age-related macular degeneration (AMD) progression risk and inform multimodal clinical imaging based on optical coherence tomography (OCT), we examined lipid content and regional prevalence of BLinD, soft drusen, pre-BLinD, and subretinal drusenoid deposit (SDD) in AMD and non-AMD aged eyes. We estimated BLinD volume and illustrated its relation to type 1 macular neovascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 101 publications
(154 reference statements)
6
44
0
Order By: Relevance
“…Characteristic extracellular deposits (drusen, subretinal drusenoid deposits) form between photoreceptors and their choroidal and retinal blood supplies. 3 …”
mentioning
confidence: 99%
“…Characteristic extracellular deposits (drusen, subretinal drusenoid deposits) form between photoreceptors and their choroidal and retinal blood supplies. 3 …”
mentioning
confidence: 99%
“…Later, Greferath et al reported the first clinicopathologic correlation of RPD in an eye imaged with OCT during lifetime confirming that RPD represent subretinal deposits that extend through the outer nuclear layer and compromise photoreceptor integrity 4 . Unlike RPD, soft drusen are lipid-rich extracellular material localized between the basal lamina of the RPE and the inner collagenous layer of Bruch’s membrane 5 . The exact pathophysiology of RPD formation and the progressing of outer retinal degeneration spatially associated with RPD lesions are currently subject of intensive research 6 .…”
Section: Introductionmentioning
confidence: 99%
“…AMD affects vertically integrated cellular layers formed by light-sensing photoreceptors and support cells (retinal pigment epithelium (RPE), choriocapillaris, MĂĽller glia). Characteristic extracellular deposits (drusen, subretinal drusenoid deposits) form between photoreceptors and their choroidal and retinal blood supplies ( 3 ). RPE cells supporting photoreceptors and vessels are central to, and impacted by, both atrophic and neovascular AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic extracellular deposits (drusen, subretinal drusenoid deposits) form between photoreceptors and their choroidal and retinal blood supplies. 3 AMD is increasingly understood via clinical optical coherence tomography (OCT).…”
Section: Introductionmentioning
confidence: 99%